2011
DOI: 10.3390/d3020235
|View full text |Cite
|
Sign up to set email alerts
|

Invasion Age and Invader Removal Alter Species Cover and Composition at the Suisun Tidal Marsh, California, USA

Abstract: Abstract:Wetland ecosystems are vulnerable to plant species invasions, which can greatly alter species composition and ecosystem functioning. The response of these communities to restoration can vary following invader removal, but few studies have evaluated how recent and long-term invasions can affect the plant community's restoration potential. Perennial pepperweed (Lepidium latifolium) has invaded thousands of hectares of marshland in the San Francisco Estuary, California, United States of America, while th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Terrestrial vertebrates, such as feral cats (Felis catus) and house mice, affect the species through predation and competition, respectively. Invasive plants are a large concern (USFWS 2013); species such as smooth cordgrass (Spartina alterniflora), common reed (Phragmites australis), and perennial pepperweed (Lepidium latifolium) alter habitat structure and may displace native flora and fauna (Takekawa et al 2006;Estrella and Kneitel 2011;Wigginton et al 2014). Aquatic invasive plants can alter flows and displace native species in the estuary, which affects SMHM habitat (Moyle et al 2010).…”
Section: Threatsmentioning
confidence: 99%
“…Terrestrial vertebrates, such as feral cats (Felis catus) and house mice, affect the species through predation and competition, respectively. Invasive plants are a large concern (USFWS 2013); species such as smooth cordgrass (Spartina alterniflora), common reed (Phragmites australis), and perennial pepperweed (Lepidium latifolium) alter habitat structure and may displace native flora and fauna (Takekawa et al 2006;Estrella and Kneitel 2011;Wigginton et al 2014). Aquatic invasive plants can alter flows and displace native species in the estuary, which affects SMHM habitat (Moyle et al 2010).…”
Section: Threatsmentioning
confidence: 99%
“…First, competition for water and other resources further reduces native species density, biomass, and species richness of a site [35]. This is followed by reduction in native species growth, which depletes the native seedbank and, finally, subtle changes of soil biological and chemical properties may occur that hinder repopulation by native plants [36].…”
Section: Introductionmentioning
confidence: 99%
“…smooth brome, Kentucky bluegrass, or warm-season grasses) also influences community composition response to different burn timings [24]. Results from these diverse studies indicate that individual plant and community responses to burn timing could assist or hamper land managers in their goal to manipulate species composition.A second method of influencing grassland composition is adding or withholding nutrients, with or without prescribed burns [24][25][26][27][28][29][30][31][32][33][34][35][36]. Burning changes nutrient cycling [26,27].…”
mentioning
confidence: 99%
“…In addition, plants may have altered the ecosystem and abiotic processes (e.g. soil salt content) such that pre-invasion communities cannot be restored (Busch and Smith 1993;Estrella and Kneitel 2011;Kerns et al 2009;Tomanek and Ziegler 1962). Therefore, the best defense against saltcedar is to identify and remove plants before they become well-established.…”
mentioning
confidence: 97%
“…Greater control often is achieved at less expense when perennial weeds are treated as seedlings, immature plants, or in young stands (Estrella and Kneitel 2011;Smith et al 2002;Westbrooks 2004) yet only a few control techniques are reported for young (a few weeks to one growing-season old) saltcedar plants. Flooding has been reported to control saltcedar plants between 4 and 10 wk old if completely submerged for .25 d (Gladwin and Roelle 1998;Horton et al 1960;Sprenger et al 2001).…”
mentioning
confidence: 99%